Sustainable Tourism in Small Communities: Opportunities and Challenges in Inowłódz Municipality - Waldemar CUDNY; Zuzanna MIKSA (Communications of International Proceedings, 2024)
The article analyzes the potential of the Inowłódz Municipality, located in central Poland, to foster sustainable tourism. Today, sustainability is crucial in tourism development at global, regional, and local levels. This study is based on field observations conducted by the authors, questionnaire surveys among local communities and tourists, and a SWOT analysis. These methods were used to assess tourist attractions, identify them as key elements of the area's tourism potential, and evaluate the prospects for developing sustainable tourism in the Inowłódz Municipality. The research showed that the Inowłódz Municipality has high tourism potential. The main factors shaping this potential include rich natural attractions, such as rivers and protected natural areas. In addition to its natural attractions, the municipality offers many human-made attractions, such as historical and military sites and cultural-entertainment events. The Inowłódz Municipality possesses significant tourism potential, but further efforts are required to fully realize this potential by strengthening sustainable tourism practices and creating related tourism products.
Keywords: Sustainable tourism; tourst attractions; small communities; Inowłódz; Poland